PH-responsive strontium nanoparticles for targeted gene therapy against mammary carcinoma cells - Bakhtiar, Athirah (Asian J Pharm Sci, 2021)
Genetic intervention via the delivery of functional genes such as plasmid DNA (pDNA) and short-interfering RNA (siRNA) offers a great way to treat many single or multiple genetic defects effectively, including mammary carcinoma. Delivery of naked therapeutic genes or siRNAs is, however, short-lived due to biological clearance by scavenging nucleases and circulating monocytes. Low cellular internalization of negatively-charged nucleic acids further causes low transfection or silencing activity. Development of safe and effectual gene vectors is therefore undeniably crucial to the success of nucleic acid delivery. Inorganic nanoparticles have attracted considerable attention in the recent years due to their high loading capacity and encapsulation activity. Here we introduce strontium salt-based nanoparticles, namely, strontium sulfate, strontium sulfite and strontium fluoride as new inorganic nanocarriers. Generated strontium salt particles were found to be nanosized with high affinity towards negatively-charged pDNA and siRNA. Degradation of the particles was seen with a drop in pH, suggesting their capacity to respond to pH change and undergo dissolution at endosomal pH to release the genetic materials. While the particles are relatively nontoxic towards the cells, siRNA-loaded SrF(2) and SrSO(3) particles exerted superior transgene expression and knockdown activity of MAPK and AKT, leading to inhibition of their phosphorylation to a distinctive extent in both MCF-7 and 4T1 cells. Strontium salt nanoparticles have thus emerged as a promising tool for applications in cancer gene therapy.